PENGATURAN PERLINDUNGAN HUKUM PADA PERJANJIAN E-CONTRACT PINJAM MEMINJAM UANG PADA LAYANAN FINANCIAL TECHNOLOGY BERBASIS PEER TO PEER LENDING - PUTRI, INDIRA HANAYA (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The development of globalization has encouraged the birth of the digital era of technology, and the presence of Financial Technology (Fintech). One of the features used is money lending, then information technology-based money lending and borrowing services or Peer to Peer Lending (P2PL) emerged, regulated in Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services (LPMUBTI) . The form of bond in fintech contained in an electronic contract arises as a result of an agreement between the Organizer and the Lender, or the Lender and the Loan Recipient. This research is normative juridical, as an approach to exploring law based on statutory regulations. The nature of the research used is descriptive research, aiming to describe clearly and in detail all the information obtained regarding the research subject, namely Fintech P2PL. The research results show that the protection of the parties in P2PL fintech is very lacking, namely loan recipients who lack education regarding P2PL fintech cause losses in default. Nor can lenders lose their money if bad credit occurs.Keyword: Legal Protection, Financial Technology, Peer to Peer Lending